2007
DOI: 10.1182/blood-2007-03-079673
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic significance of allelic imbalance by single-nucleotide polymorphism analysis in low-risk myelodysplastic syndromes

Abstract: Low-risk myelodysplastic syndrome (MDS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
148
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(160 citation statements)
references
References 34 publications
11
148
1
Order By: Relevance
“…Although karyotyping analysis with SNP-A have been used in the past, 34 the current study differs in several important and critical aspects compared with the initial report by Gondek et al 14 and Mohamedali et al 18 First, this study emphasizes the complementary usage of both MC and SNP-A, whereas the original studies of For personal use only. on May 11, 2018.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Although karyotyping analysis with SNP-A have been used in the past, 34 the current study differs in several important and critical aspects compared with the initial report by Gondek et al 14 and Mohamedali et al 18 First, this study emphasizes the complementary usage of both MC and SNP-A, whereas the original studies of For personal use only. on May 11, 2018.…”
Section: Discussionmentioning
confidence: 73%
“…14,18 Our protocol involved exclusion of known nonclonal germline-encoded CNVs and CN-LOH and the confirmation of new somatic defects with the use of paired nonclonal cells (supplemental Figure 1A-B). We performed SNP-A 6.0 arrays on 228 samples, 250K arrays on 200 samples and 50K arrays in 2 samples.…”
Section: Snp-a-based Karyotyping As a Reliable Diagnostic Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…One SNP array study of 119 lowrisk MDS patients, 77 with a normal karyotype, 36 with visible cytogenetic alterations and 6 with unavailable cytogenetics, identified 125 UPDs with a median size of 3.78 Mb in 46% of the cases studied. 8 Another study showed that 82% of MDS patients harbor gains and losses detected by SNP arrays, whereas conventional cytogenetics detected alterations in 50%. 9 In addition, UPD was found in 33% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…In both studies, first correlations of genomic imbalances including UPD with survival indicated that the presence of these may correlate with a shorter survival. 8,9 This high rate of UPDs in MDS was recently challenged in a study that showed, when using buccal DNA samples from the same patients as controls, that only a small number of the potential loss of heterozygosity regions represent tumor-specific UPDs and gains and losses. 10 In that report only 4/33 cytogenetically normal cases had additional alterations.…”
Section: Introductionmentioning
confidence: 99%